IMPLEMENTATION OF THE COMPLEX PROPORTIONAL ASSESSMENT METHOD IN DETERMINING THE PLACE OF INDUSTRIAL WORK PRACTICE - Suwinda Aulansari; Muhammad Dedi Irawan (JIKO (Jurnal Informatika dan Komputer), 2024)
Industrial Work Practices are a form of directly applying the knowledge gained in the classroom to the industrial world or the world of work. However, in its implementation, problems exist, such as workloads that must be by majors and conditions. This research uses the COPRAS method to build a decision support system to determine the place of industrial work practice at Prama Artha Private Vocational School. This method focuses on resolving each alternative's relative weight and utility and performing complex calculations proportionally. This study used 10 alternative data for internship places as samples and five criteria: student expertise, company division, distance, number of students, and type of company. The results of this study are that the PLN UP3 Pematang Siantar alternative is ranked first with a final calculation result of 100, the USI Pematang Siantar alternative is ranked second with a final calculation result of 96.29 and continued with the Tunas Bangsa STIKOM alternative with a final calculation value of 93.01. This COPRAS ranking system is based on the weights and values given to each criterion so that objectivity and accuracy are guaranteed in determining the place of internship based on the needs and abilities of students. Based on the results of black box testing of the system, it can be concluded that the system as a whole can run according to functionality and is ready for use